2007
DOI: 10.1111/j.1467-7660.2007.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Political Cleaners: Women as the New Anti‐Corruption Force?

Abstract: There is currently a myth in the making: that women are less corrupt than men. Recently some aid donors have cited statistical evidence that countries with larger numbers of women in politics and in the workforce have lower levels of corruption. That this finding can be explained by the fact that there are more women in politics and the workforce in liberal democracies that are anyway less corrupt than poorer less liberal regimes does not detract from the eagerness with which some development actors are seizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(94 citation statements)
references
References 20 publications
3
82
0
9
Order By: Relevance
“…Alhassan-Alolo (2007) finds using data on hypothetical scenarios that females did not exude higher ethical standards than men and argues that women may not necessarily prove to be less corrupt than men when exposed to environments characterized by corrupt opportunities and networks. A similar argument can be found in Goetz (2007).…”
Section: Covariatessupporting
confidence: 56%
“…Alhassan-Alolo (2007) finds using data on hypothetical scenarios that females did not exude higher ethical standards than men and argues that women may not necessarily prove to be less corrupt than men when exposed to environments characterized by corrupt opportunities and networks. A similar argument can be found in Goetz (2007).…”
Section: Covariatessupporting
confidence: 56%
“…For example, Goetz (2007) suggests that greater female participation in government is associated with lower corruption and is driven by the relative exclusion of women from networks traditionally dominated by men. Women are also found to be less likely to be asked for a bribe (Mocan, 2008).…”
Section: H1mentioning
confidence: 99%
“…Si es cierto que las mujeres participan menos 12 Según Redlawsk y McCann, las mujeres y los ciudadanos más mayores aplican la etiqueta de corrupción a un mayor número de comportamientos políticos aunque estos no sean estrictamente ilegales (2002). 13 Otros autores defi enden que esta relación es espuria y que está causada por los efectos de la democracia liberal (igualdad de género y mejor gobernanza) y no por la mayor presencia de mujeres (Sung, 2003;Goetz, 2007). en actividades corruptas es lógico pensar que tampoco apoyarán actividades de este tipo.…”
Section: Género Y Edadunclassified
“…13 Other authors hold that this relationship is spurious and that it is caused by the effects of liberal democracy (gender equality and better governance), and not by the greater presence of women (Sung, 2003;Goetz, 2007 Age also has an impact on justifying corruption. In a longitudinal study using data from eight European countries, Torgler and Valev (2006) found that, after controlling for the cohort effects, young people under 30 are more likely to perceive corruption as a justifi able fact than citizens over that age.…”
Section: Gender and Agementioning
confidence: 99%